Effects of Radial Extracorporeal Shock Wave Therapy on Flexor Spasticity of the Upper Limb in Post-stroke Patients: Study Protocol for a Randomized Controlled Trial - Fan, Tao; Zhou, Xiangying; He, Peichen; Zhan, Xiaojia; Zheng, Peng; Chen, Rong; Li, Rongdong; Li, Rihui; Wei, Mingyang; Zhang, Xue; Huang, Guozhi (Frontiers in Neurology, 2021)
Background: Flexor spasticity of the upper limb is common in poststroke patients and seriously affects the recovery of upper limb function. However, there are no standard management protocols for this condition. Radial extracorporeal shock wave therapy (rESWT) is widely used for various diseases, some studies reported the effects of ESWT on reducing spasticity, but the mechanism of ESWT to reduce spasticity by affecting the excitability of stretch reflex or non-neural rheological components in spastic muscles or both is not yet clear. A large randomized controlled trial with comprehensive evaluation indicators is still needed. The study is to observe the effect of rESWT on flexor spasticity of the upper limb after stroke and explore its mechanism. Methods: A prospective, randomized, double-blind controlled trial is to be performed. One hundred participants will be recruited from the Inpatient Department of Zhujiang Hospital. Eligible patients will be randomly allocated to either receive three sessions of active rESWT (group A) or sham-placebo rESWT (group B) with 3-day intervals between each session. Assessment will be performed at baseline and at 24 h after each rESWT (t1, t2, and t3). The primary assessment outcome will be the Modified Ashworth Scale, and other assessments include surface electromyography, MyotonPRO digital muscle function evaluation, and infrared thermal imaging. All data will be analyzed using intention-to-treat principles. Multiple imputation by chained equations will be used to address missing data caused by loss to follow-up and nonresponses. Per protocol, analyses will also be performed on the participants who complete other assessments. Statistical analysis will be performed using SPSS software (version 20.0) and the significance level set at p < 0.05. Discussion: This trial aims to analyze the application of rESWT for the management of spasticity after stroke via appropriate assessments. We hypothesized that after receiving active rESWT, patients would show greater improvement of upper limb muscles compared with patients within the sham-placebo group. The rESWT would be an alternative to traditional methods, and the results of this study may provide support for the further study of potential mechanisms. Clinical Trial Registration:www.chictr.org.cn, identifier: ChiCTR1800016144.